2011
DOI: 10.4049/jimmunol.1001461
|View full text |Cite
|
Sign up to set email alerts
|

Casein α s1 Is Expressed by Human Monocytes and Upregulates the Production of GM-CSF via p38 MAPK

Abstract: Caseins are major constituents of mammalian milks that are thought to be exclusively expressed in mammary glands and to function primarily as a protein source, as well as to ameliorate intestinal calcium uptake. In addition, proinflammatory and immunomodulatory properties have been reported for bovine caseins. Our aim was to investigate whether human casein α s1 (CSN1S1) is expressed outside the mammary gland and possesses immunomodulatory functions in humans as well. For this purpose, CSN1S1 mRNA was detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 59 publications
0
34
0
Order By: Relevance
“…Our finding that a variant of FGFR1 is associated with type 2 diabetes is supportive of such a possibility. Casein α S1 (CSN1S1) is a member of the casein family that has been shown to possess proinflammatory properties, such as the upregulation of IL-1β [45]. Data from animal studies and clinical trials is suggestive of a causative role for IL-1β in the loss of beta cell mass in type 2 diabetes [46].…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that a variant of FGFR1 is associated with type 2 diabetes is supportive of such a possibility. Casein α S1 (CSN1S1) is a member of the casein family that has been shown to possess proinflammatory properties, such as the upregulation of IL-1β [45]. Data from animal studies and clinical trials is suggestive of a causative role for IL-1β in the loss of beta cell mass in type 2 diabetes [46].…”
Section: Discussionmentioning
confidence: 99%
“…This might suggest a more recent antigenic stimulus. It has recently been shown, that human CSN1S1 is expressed in human monocytes and induces pro-inflammatory cytokines [15]. Such ectopic expression of CSN1S1 could potentially be an explanation for the IgM mediated reaction on human CSN1S1 observed in the corresponding SD ELISA for a few sera.…”
Section: Discussionmentioning
confidence: 93%
“…Human CSN1S1 is expressed in monocytes and stimulates the expression of proinflammatory cytokines e.g. GM-CSF [15].…”
Section: Introductionmentioning
confidence: 99%
“…30 μg/ml polymyxin (Sigma-Aldrich, Munich, Germany) was added to experiments to exclude any LPS effects (Sigma-Aldrich) [13], except for the assessment of cellular morphology of living cells, where 200 ng/ml LPS was added in a control experiment. Recombinant human casein alpha S1 (CSN1S1) (Calbiochem, Darmstadt, Germany) was added to cultured cells in indicated concentrations for 24 or 120 h. The following compounds were used to induce in vitro differentiation of monocytes as control experiments: M-CSF (R&D Systems, Wiesbaden, Germany) 50 ng/ml, GM-CSF 50 ng/ml, IL-4 20 ng/ml, IFNγ 10 ng/ml (all CellGenix, Freiburg, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, independent studies reported overexpression of CSN1S1 in synovial tissue of patients with osteoarthritis and rheumatoid arthritis [10-12]. Consequently, a potential function of CSN1S1 was further characterized by the finding of proinflammatory effects on monocytic cells, like for instance increased expression of IL-1β [13]. Thus, the concept of CSN1S1 as a multifunctional protein with both nutritional and immunomodulatory functions is evolving.…”
Section: Introductionmentioning
confidence: 99%